Research on professional learning margin of university information security teachers in China - Yuan MENG; Pei-qun WU (网络与信息安全学报)
Analyzing the educational background features of China’s university information security teachers can provide reference for the teaching staff construction of cyberspace security discipline.Based on the result of a national survey,Web content analysis was used to approach to analyze the resumes of information security teachers from Internet.The result shows that these teachers are mainly computer,mathematics,telecommunication and electronics majors,from undergraduate to master,doctorate,postdoctoral,their professional gradually to the information security professional gathering.